Hubungan Literasi Sains dan Berpikir Kritis dengan Self-Awareness Siswa pada Materi Pencemaran Lingkungan - Lusy Fajarwati; Neneng Windayani; Wati Susilawati (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2025)
This study aims to analyze the relationship between science literacy, critical thinking skills, and students' self-awareness in learning about environmental pollution. The research method used is a quasi-experiment involving 32 seventh-grade students as respondents. Data were collected through a problem-based test consisting of 20 multiple-choice questions to measure science literacy and critical thinking skills, as well as a Likert scale questionnaire to evaluate self-awareness. Data analysis was performed using multiple regression techniques. The results of the study show that science literacy and critical thinking skills have a positive and significant relationship with students' self-awareness. The better the students' science literacy and critical thinking skills, the higher their self-awareness, especially in understanding and addressing environmental issues. The conclusion of this study is that improving science literacy and critical thinking skills significantly enhances students' self-awareness, which is an important element in issue-based environmental learning. This research provides insights for educators to integrate science literacy and critical thinking skills into relevant and contextual learning strategies. This effort is expected to create a generation of students who are more aware of their roles and responsibilities in preserving the environment.